Regional Original Potential and Income in terms of Tourism towards Micro, Small and Medium Enterprises (MSMEs) to International Products (Hotel Tax, Restaurant Tax) - Muchammad Firman Mauludin; Sudarmiatin; Rosmiza Bidin (Institute of Computer Science (IOCS), 2022)
For this study, the writing of this research uses writing and managing the data by analyzing descriptive historical data and qualitative analysis with a combination of several recommendations from several inputs and analyzes obtained with the latest state of development. Descriptive analysis related to taxpayer collection data, and the contribution value of regional original income.